Associations of the MAOA uVNTR genotype and 5-HTTLPR/rs25531 haplotype with psychopathic traits. (September 2021) - Hollerbach, Pia; Olderbak, Sally; Wilhelm, Oliver; Montag, Christian; Jung, Sonja; Neumann, Craig S.; Habermeyer, Elmar; Mokros, Andreas
Abstract: Previous studies have linked polymorphisms of the monoamine oxidase A ( MAOA uVNTR) and serotonin transporter gene ( 5-HTTLPR ) to individual differences in the expression of psychopathic traits, but findings remain inconsistent. One possible reason is that these studies have treated psychopathy as a unitary construct when there is accumulating evidence that there are variants or subtypes. We used a variable-centered and a person-centered approach by (a) examining putative genetic correlates of psychopathy across individuals and (b) comparing the frequencies of the MAOA uVNTR genotype and 5 -HTTLPR/rs25531 haplotype between empirically derived subtypes of psychopathy, respectively. Notably, we included the often neglected rs25531 polymorphism, which is closely connected to the 5-HTTLPR . Based on data from male offenders and community volunteers, structural equation modeling indicated that the 5-HTTLPR/rs25531 haplotype was specifically associated with interpersonal deficits beyond the overarching psychopathy construct. Latent profile analysis revealed four clusters that were labeled non-psychopaths, sociopaths, callous-conning, and psychopaths. The low-activity variant of the 5- HTTLPR/rs25531 haplotype was significantly more frequent in the callous-conning compared to the non-psychopathic subtype. There were no effects for the MAOA uVNTR. The results illustrate that psychopathy should not be treated as a unitary construct but that there are variants with specific profiles of psychopathic traits, and that the 5-HTTLPR/rs25531 haplotype plays a role in the manifestation of interpersonal deficits from a variable-centered as well as from a person-centered view. Highlights: Individuals with a low-activity variant of the 5-HTTLPR/rs25531 show higher levels of interpersonal deficits. We replicated four profiles: non-psychopaths, sociopaths, callous-conning, and psychopaths. There are differences between the callous-conning and non-psychopathic profiles regarding 5-HTTLPR/rs25531distribution.